PENGARUH POLA ASUH ORANG TUA DAN SELF–CONCEPT TERHADAP KEMANDIRIAN BELAJAR SISWA KELAS IV DI SD KAPANEWON SAMIGALUH - Nonik Wus Rahayu; Maximus Gorky Sembiring; Septian Aji Permana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study explores the influence of parental upbringing and self-concept on the learning independence of fourth-grade students at SD Kapanewon Samigaluh during the 2023/2024 academic year. A descriptive quantitative method with a survey approach was employed to investigate causal relationships and test hypotheses regarding factors affecting learning independence. Proportionate Random Sampling was used to select 158 students from 26 schools in Kapanewon Samigaluh. Data were collected using a 42-item questionnaire measuring parental upbringing, self-concept, and learning independence. Validity was established through Pearson Product Moment correlation, and reliability was assessed using Cronbach's Alpha, yielding a coefficient greater than 0.6. The analysis revealed that supportive parental upbringing and a positive self-concept significantly influence students' learning independence. Specifically, parental upbringing characterized by emotional support, consistent control, and a positive self-concept significantly enhance students' learning independence. These findings emphasize the importance of supportive parental upbringing and a positive self-concept in fostering learning independence among students at SD Kapanewon Samigaluh.